Alice and Greta's color magic - Simmons, Steven J., 1946-; Moore, Cyd (New York : Knopf, 2001)
After Greta, a naughty witch, causes trouble by casting a spell that drains all color from the world, she must team up with Alice, a kind witch, to set things right.
Keywords: Magic -- Fiction; Witches -- Fiction; Color -- Fiction